High-entropy alloy pole piece and preparation method and application thereof

By preparing multi-element high-entropy alloy electrodes through electrochemical deposition, the problems of poor cycle stability and rate performance of high-entropy alloy materials in lithium batteries are solved, achieving high-efficiency and low-cost performance improvement of lithium batteries and suppressing lithium dendrite growth and volume expansion.

CN120878756APending Publication Date: 2025-10-31ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511024551.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing high-entropy alloy materials suffer from poor cycle stability and rate performance in lithium batteries. Furthermore, traditional preparation methods are costly and time-consuming, making it difficult to meet the high-performance requirements of lithium batteries.

Method used

A multi-element high-entropy alloy electrode was prepared in an aqueous system using an electrochemical deposition method. By controlling the multi-valence metal elements, a high configurational entropy stable phase was formed and deposited onto the surface of a conductive substrate to form a high-entropy alloy layer, thereby optimizing the alloy structure and composition.

Benefits of technology

It improves the cycle life and rate performance of lithium metal batteries, reduces the manufacturing cost, enhances the structural stability and mechanical properties of high-entropy alloy electrodes, and suppresses lithium dendrite growth and volume expansion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120878756A_ABST
    Figure CN120878756A_ABST
Patent Text Reader

Abstract

The invention provides a high-entropy alloy pole piece and a preparation method and application thereof, and belongs to the technical field of lithium ion batteries. The high-entropy alloy pole piece comprises a bottom lining and a high-entropy alloy deposited on the bottom lining, the chemical general formula of the high-entropy alloy is Ni20MaNbXcYdZe, the high-entropy alloy comprises rare earth metal or / and scattered metal, a, b, c, d and e respectively represent atomic percentages of corresponding metal elements, a is larger than or equal to 5 and smaller than or equal to 35, c is larger than or equal to 5 and smaller than or equal to 35, and e is larger than or equal to 5 and smaller than or equal to 35. 10 < = b < = 40; 6 < = c < = 35; 0.1 < = d < = 10; 0 < = e < = 10; a + b + c + d + e = 80; m is a monovalent metal, N is a divalent metal, X is a trivalent La series metal, Y is a tetravalent metal, and Z is a pentavalent metal. The structural stability and the mechanical performance of the prepared high-entropy alloy pole piece are improved, the lithium nucleation overpotential can be effectively reduced through regulation and control over the multivalent rare earth and the scattered metal, lithium ions are promoted to be evenly deposited on the surface of a negative electrode, and then growth and volume expansion of lithium dendrites are inhibited. The prepared high-entropy alloy negative electrode can be used for prolonging the cycle life and improving the rate capability of a lithium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of lithium-ion batteries, and particularly relates to a negative electrode material. Background Technology

[0002] Lithium metal anodes are considered key to improving battery energy density due to their significant advantages, including high theoretical specific capacity (3860 mAh / g), low electrochemical potential (-3.04 V), and high reactivity. However, the technology is not yet fully mature, and safety risks and high costs during preparation and use, such as lithium dendrite penetration, volume expansion, and dead lithium, limit their large-scale application to some extent. Therefore, the concept of electrodeless lithium metal batteries (AFLMB) has been introduced. Electrodeless lithium metal batteries eliminate the anode material found in traditional lithium metal batteries, fully utilizing the potential of lithium-containing cathodes to maximize volumetric and gravimetric energy density, thereby reducing battery production and maintenance costs.

[0003] Electrodeless lithium metal batteries are essentially a special type of lithium metal battery. Their practical application is still affected by issues such as lithium dendrite formation, interfacial side reactions, and SEI film rupture, leading to capacity decay and shortened cycle life. Research shows that modifying electrodeless lithium metal batteries through multi-metal or high-entropy alloy regulation to achieve uniform lithium deposition / extraction is key to effectively preserving active lithium and improving battery cycle stability and safety. High-entropy alloys (HEAs) are composed of five or more principal elements. Their unique "cocktail effect," multi-element synergistic effect, lattice distortion, and unique thermodynamic properties can significantly improve problems such as volume expansion, dendrite growth, and interfacial cycle stability in lithium metal anodes. Currently, the main methods for preparing high-entropy alloys include high-energy ball milling, melting, and magnetron sputtering. These methods have strict requirements for experimental preparation environments, high preparation costs, long cycles, and high energy consumption, and their practicality and industrial applicability are relatively low. For example, patent publication number CN 119447197A discloses a method for preparing a lithium metal anode with an ultrathin lithium-loving high-entropy alloy interface layer. This method involves dispersing a high-entropy alloy composite material coated with carbon nanotubes, lithium-tin alloy powder, and a hydrophobic polymer in a non-organic solvent, coating it onto a copper foil, and drying it to obtain an ultrathin, pre-lithiated, and lithium-loving high-entropy alloy interface layer anode. Patent publication number CN 119419256A discloses a high-entropy alloy structured composite anode material, its preparation method, and a lithium metal battery. This high-entropy alloy structured composite anode material includes lithium, non-metallic elements, and other metallic elements. In the composite anode material, lithium atoms account for 40 at%-80 at% of the total atoms, non-metallic elements account for 1 at%-20 at% of the total atoms, and the remainder is other metallic elements in equal atomic proportions. The high-entropy alloy liquid is obtained by melting lithium metal and compounds or elements of other metallic elements, maintaining the temperature, pouring it into a mold, and cooling it to obtain a high-entropy alloy sheet.

[0004] In the field of high-entropy alloy research, the significant impact of crystal phase structure and preparation methods on the electrochemical performance of lithium-ion batteries has become a crucial issue that cannot be ignored. Precisely because the crystal phase structure and preparation methods of high-entropy alloys have such a significant and complex influence on the electrochemical performance of lithium-ion batteries, existing high-entropy alloy materials still have many limitations in meeting the high-performance requirements of lithium-ion batteries. For example, some high-entropy alloys, while possessing high capacity, exhibit poor cycle stability; others have good cycle performance but perform poorly in rate performance. Therefore, the development of a new high-entropy alloy is urgently needed. This new high-entropy alloy requires optimization in its crystal phase structure, perhaps by controlling the proportion of different crystal phases to achieve a balance between plasticity, conductivity, and spatial adaptability. Simultaneously, innovation in preparation methods is also necessary to obtain materials with more uniform composition and fewer defects, thereby significantly improving the electrochemical performance of lithium-ion batteries, including increasing capacity, enhancing cycle stability, and improving rate performance, to meet the urgent needs of the new energy sector for high-performance lithium-ion batteries. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention proposes a high-entropy alloy electrode, its preparation method, and its applications. Under aqueous conditions, a multi-element high-entropy alloy and its electrode are prepared via electrochemical deposition. This method is cost-effective, simple to operate, and has a short experimental cycle, improving the industrial applicability of the experimental results. The prepared high-entropy alloy electrode exhibits improved structural stability and mechanical properties. Furthermore, the modulation of multi-valent rare earth and dispersed metals effectively reduces the lithium nucleation overpotential, promoting uniform lithium ion deposition on the negative electrode surface and thus inhibiting lithium dendrite growth and volume expansion. The prepared high-entropy alloy negative electrode can be used to improve the cycle life and rate performance of lithium metal batteries.

[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows:

[0007] A high-entropy alloy electrode includes a substrate and a high-entropy alloy deposited on the substrate, wherein the high-entropy alloy has the general chemical formula Ni. 20 M a N b X c Y d Z e It includes rare earth metals and / or rare dispersed metals, where a, b, c, d, and e represent the atomic percentages of the corresponding metal elements, wherein 5≤a≤35; 10≤b≤40; 6≤c≤35; 0.1≤d≤10; 0≤e≤10; a+b+c+d+e=80; M is a monovalent metal, N is a divalent metal, X is a trivalent La-series metal, Y is a tetravalent metal, and Z is a pentavalent metal.

[0008] M is selected from one or more of Li, Na, and Ag; N is selected from one or more of Fe, Co, Cu, Zn, Mn, Mo, Ho, Cd, Mg, Ca, Sn, and Ba; X is selected from one or more of Al, Ga, In, Yb, Y, and Sc; Y is selected from one or more of Zr, Hf, and Ti; and Z is selected from one or more of Ta, V, and Nb.

[0009] A method for preparing a high-entropy alloy electrode includes the following steps:

[0010] (1) Under the conditions of 20~150℃, the surfactant, buffer and complexing agent are dissolved in deionized water to obtain mixed preparation solution A;

[0011] (2) Dissolve five or more soluble metal salts and reducing agents in solution A, stir at 25-200℃ for 0.2-48h, and after all the reagents have been dissolved, adjust the pH of the solution to 0.2-8.6 to obtain electrodeposition solution B;

[0012] (3) The substrate material is placed in electrodeposition solution B for constant current electrodeposition to obtain high entropy alloy electrode sheets.

[0013] The surfactant is one or more of stearic acid, sodium dodecylbenzenesulfonate, sulfated castor oil, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyethyleneimine, polyvinyl alcohol, alkylphenol polyoxyethylene ether, and triethanolamine; the buffer is one or more of boric acid, acetic acid, acetic acid, sodium acetate, disodium hydrogen phosphate, sodium dihydrogen phosphate, 2-morpholine ethanesulfonic acid, and sodium carbonate; the complexing agent is one or more of citric acid, citric acid hydrate, trisodium citrate, sodium cyanide, potassium pyrophosphate, sodium pyrophosphate, ethylenediamine, triethanolamine, oxalic acid, and gluconic acid; and the reducing agent is one or more of ascorbic acid, sodium phosphite, sodium saccharin, dimethylamineborane, sodium borohydride, sodium hypophosphite, and formaldehyde.

[0014] The soluble metal salt is a Ni-containing metal ion. + M + N 2+ X 3+ Y 4+ Z 5+ One or more of the following: chloride salts, chloride salt hydrates, nitrates, nitrate salt hydrates, sulfates, and sulfate salt hydrates.

[0015] The concentrations of soluble metal salts in the electrodeposition solution B are as follows: nickel salt 0.005–0.61 mol / L, M salt 0.001–0.82 mol / L, N salt 0.004–0.86 mol / L, X salt 0.0035–0.5 mol / L, Y salt 0.0005–0.1 mol / L, Z salt 0.0003–0.1 mol / L; surfactant concentration 0.002–0.15 mol / L; buffer concentration 0.006–0.43 mol / L; complexing agent concentration 0.004–0.28 mol / L; and reducing agent concentration 0.001–0.18 mol / L.

[0016] The substrate material is one or more of the following: copper foil, copper sheet, titanium sheet, silver rod, platinum sheet, copper foam, nickel foam, carbon cloth, non-woven fabric, carbon paper, carbon fiber, and porous carbon paper.

[0017] In step (3), the substrate material is etched in an acidic solution in advance. The etching is carried out in the acidic solution for 0.1 to 24 hours to obtain a hydrophilic substrate product. The substrate product is repeatedly washed with acetone and deionized water to obtain a pH neutral substrate material for later use.

[0018] The acidic solution is one or more of concentrated sulfuric acid, concentrated nitric acid, and concentrated hydrochloric acid.

[0019] The substrate material can be selectively mechanically polished and planarized before being etched with an acidic solution.

[0020] The constant current electrodeposition method is as follows: after the electrodeposition solution B is allowed to stand for 0.2–36 hours, an electrochemical deposition reaction is carried out at 20–120°C, using a graphite electrode as the counter electrode and the substrate product as the working electrode, with a current density of 1–3800 mA / cm². 2 The electrodeposition time was 0.05 to 12 hours, resulting in high-entropy alloys and high-entropy alloy electrodes based on electrodeposition.

[0021] Preferably, the electrodeposition area of ​​the high-entropy alloy is 0.5–120 × 1–180 mm. 2 .

[0022] Application of a high-entropy alloy electrode in lithium metal batteries.

[0023] The beneficial effects of this invention are:

[0024] 1. This invention uses a constant current electrodeposition method to electrodeposit five or more soluble metal salts onto the surface of a conductive substrate in an aqueous environment, forming an alloy layer with a high entropy structure. The experimental operation is simple, low-cost, and short-cycle, and it can improve the industrial applicability.

[0025] 2. The six-to-multi-element high-entropy alloy electrode prepared by electrodeposition is applied to lithium metal batteries, breaking the traditional alloy design mode of "single principal element + trace addition". By regulating the formation of a high configurational entropy (ΔS>1.5R) stable phase through multi-valence metal elements, the complex intermetallic compounds in traditional multi-element alloys are avoided, and the lattice distortion strengthening and multi-element synergistic effect are achieved.

[0026] 3. The high-entropy alloys are prepared by introducing three or more transition metals, rare earth metals and rare dispersed metals in three or more metal valence states to optimize the composition and structure of the high-entropy alloys, extending to hexa- or octa-eight ...

[0027] 4. By electrodepositing an ultrathin multi-element high-entropy alloy layer onto the surface of a carbon-based material, a lithium metal anode can be prepared to replace the lithium metal anode, thereby constructing a lithium-free lithium metal anode, improving the energy density and safety of the battery, saving costs, and having strong practicality.

[0028] 5. The multi-element high-entropy alloy-carbon-based anode prepared in this invention was applied to a lithium metal battery. At room temperature, a NiAgCoCdInYHfTa-C / / Li half-cell achieved an A / cm² voltage of 5 mA / cm². 2 Under these conditions, after 500 cycles, the coulombic efficiency is above 99.4%, and the capacity retention is 89%; 30 mA / cm 2 Under these conditions, the initial efficiency of the half-cell is 99.7%, and after 500 cycles, the coulombic efficiency is still above 99.2%, which improves the cycle and rate performance of lithium metal batteries. Attached Figure Description

[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0030] Figure 1 A flowchart illustrating the steps of the method for preparing the high-entropy alloy provided in this application.

[0031] Figure 2 This is a structural diagram of the high-entropy alloy electrode sheet in Example 3. Detailed Implementation

[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] Example 1

[0034] A high-entropy alloy material, the process flow diagram is as follows: Figure 1 As shown.

[0035] The preparation of high-entropy alloy materials includes the following steps:

[0036] A 2×2cm carbon cloth substrate was etched in concentrated acid (H₂SO₄ and HNO₃) for 3 hours, with a volume ratio of H₂SO₄ to HNO₃ of 2:1, to obtain a hydrophilic carbon cloth product. The hydrophilic carbon cloth was then ultrasonically cleaned three times successively in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At 50℃, 0.012 mol / L sodium dodecyl sulfate, 0.032 mol / L boric acid, and 0.12 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. 0.02 mol / L Ni₂SO₄·6H₂O, 0.012 mol / L CoSO₄·7H₂O, 0.008 mol / L CuSO₄·5H₂O, 0.03 mol / L Zn₂SO₄·7H₂O, and 0.06... 2 mol / L LYCl3, 0.018 mol / L TiCl4, and 0.008 mol / L ascorbic acid were dissolved sequentially in solution A above. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH of the solution was then adjusted to 2.8 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after electrodeposition solution B was allowed to stand for 1 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiCoCuZnYTi high-entropy alloy layer and a NiCoCuZnYTi-C high-entropy alloy electrode sheet based on electrodeposition.

[0037] Example 2

[0038] A method for preparing a high-entropy alloy material, comprising the following steps:

[0039] A 2×2cm carbon cloth substrate was etched in concentrated acid (H₂SO₄ and HNO₃) for 3 hours, with a volume ratio of H₂SO₄ to HNO₃ of 2:1, to obtain a hydrophilic carbon cloth product. The hydrophilic carbon cloth was then ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At 50℃, 0.013 mol / L sodium dodecyl sulfate, 0.036 mol / L boric acid, and 0.21 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. 0.06 mol / L Ni₂SO₄·6H₂O, 0.08 mol / L AgNO₃·6H₂O, 0.055 mol / L Na₂SO₄, 0.08 mol / L CuSO₄·5H₂O, and 0.08 mol / L AlCl₃· 6H₂O, 0.08 mol / L LYCl₃, 0.05 mol / L TaCl₅, and 0.012 mol / L ascorbic acid were dissolved sequentially in solution A. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH was then adjusted to 2.5 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 1 h, an electrochemical deposition reaction was carried out at 50°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 15 min, resulting in a NiAgNaCuAlYTa high-entropy alloy layer and a NiAgNaCuAlYTa-C high-entropy alloy electrode based on electrodeposition.

[0040] Example 3

[0041] A method for preparing a high-entropy alloy material, comprising the following steps:

[0042] A 2×2cm carbon cloth substrate was etched in concentrated acid (H2SO4 and HNO3) for 3 hours, with a volume ratio of H2SO4 to HNO3 of 2:1, to obtain a hydrophilic carbon cloth product. The hydrophilic carbon cloth was then ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At 50℃, 0.008 mol / L sodium dodecyl sulfate, 0.015 mol / L boric acid, and 0.09 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. 0.06 mol / L Ni2SO4·6H2O, 0.1 mol / L AgNO3·6H2O, 0.06 mol / L Co(SO4)·7H2O, 0.06 mol / L LdCl2·H2O, and 0.08 mol / L InCl3·4H2O were also prepared. 0.1 mol / L LYCl3, 0.04 mol / L HfCl4, 0.04 mol / L TaCl5, and 0.012 mol / L ascorbic acid were dissolved sequentially in solution A above. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH of the solution was then adjusted to 3 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 2 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiAgCoCdInYHfTa high-entropy alloy layer and a NiAgCoCdInYHfTa-C high-entropy alloy electrode sheet.

[0043] Example 4

[0044] A method for preparing a high-entropy alloy material, comprising the following steps:

[0045] A 2×2cm copper foam substrate was etched in concentrated acid (H₂SO₄ and HNO₃) for 3 hours, with a volume ratio of H₂SO₄ to HNO₃ of 3:1, to obtain a copper sheet substrate with an etched surface. This substrate was then ultrasonically cleaned three times with acetone and deionized water to obtain pH-neutral copper foam for later use. At 50°C, 0.009 mol / L sodium dodecyl sulfate, 0.008 mol / L boric acid, and 0.12 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. 0.06 mol / L NiCl₂·6H₂O, 0.08 mol / L FeSO₄·7H₂O, 0.09 AgNO₃·6H₂O, 0.09 mol / L ZnSO₄·7H₂O, and 0.1 mol / L A were then added. LCl3·6H2O, 0.03 mol / L HfCl4, and 0.008 mol / L ascorbic acid were dissolved sequentially in solution A above. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH of the solution was then adjusted to 3.2 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 1 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and copper foam as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiFeAgCrAlHf high-entropy alloy layer and a NiFeAgCrAlHf-CuF high-entropy alloy electrode sheet based on electrodeposition.

[0046] Example 5

[0047] A high-entropy alloy material, the preparation of which includes the following steps:

[0048] A 2×2cm carbon cloth substrate was etched in concentrated acid (H₂SO₄ and HNO₃) for 3 hours, with a volume ratio of H₂SO₄ to HNO₃ of 2:1, to obtain a hydrophilic carbon cloth product. The hydrophilic carbon cloth was then ultrasonically cleaned three times successively in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At 50℃, 0.012 mol / L sodium dodecyl sulfate, 0.032 mol / L boric acid, and 0.12 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. 0.02 mol / L Ni₂SO₄·6H₂O, 0.012 mol / L CoSO₄·7H₂O, 0.008 mol / L CuSO₄·5H₂O, 0.03 mol / L Zn₂SO₄·7H₂O, and 0.06... 2 mol / L LYCl3, 0.018 mol / L LTiCl4, and 0.008 mol / L ascorbic acid were dissolved sequentially in solution A above. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH of the solution was then adjusted to 6.8 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after electrodeposition solution B was allowed to stand for 1 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiCoCuZnYTi high-entropy alloy layer and a NiCoCuZnYTi-C high-entropy alloy electrode sheet based on electrodeposition.

[0049] Example 6

[0050] A method for preparing a high-entropy alloy material, comprising the following steps:

[0051] A 2×2cm carbon cloth substrate was etched in concentrated acid (H₂SO₄ and HNO₃) for 3 hours, with a volume ratio of H₂SO₄ to HNO₃ of 2:1, to obtain a hydrophilic carbon cloth product. The hydrophilic carbon cloth was then ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At 50℃, 0.013 mol / L sodium dodecyl sulfate, 0.036 mol / L boric acid, and 0.21 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. 0.06 mol / L Ni₂SO₄·6H₂O, 0.08 mol / L AgNO₃·6H₂O, 0.055 mol / L Na₂SO₄, 0.08 mol / L CuSO₄·5H₂O, and 0.08 mol / L AlCl₃·6H₂O were also prepared. H₂O, 0.08 mol / L LYCl₃, 0.05 mol / L TaCl₅, and 0.012 mol / L ascorbic acid were dissolved sequentially in solution A. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH was then adjusted to 2.5 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 1 h, an electrochemical deposition reaction was carried out at 50°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 50 mA / cm². 2 The electrodeposition time was 15 min, resulting in a NiAgNaCuAlYTa high-entropy alloy layer and a NiAgNaCuAlYTa-C high-entropy alloy electrode based on electrodeposition.

[0052] Example 7

[0053] A method for preparing a high-entropy alloy material, comprising the following steps:

[0054] A 2×2cm carbon cloth substrate was etched in concentrated acid (H₂SO₄ and HNO₃) for 3 hours, with a volume ratio of H₂SO₄ to HNO₃ of 2:1, to obtain a hydrophilic carbon cloth product. The hydrophilic carbon cloth was then ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At 50℃, 0.008 mol / L sodium dodecyl sulfate, 0.015 mol / L boric acid, and 0.09 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. 0.06 mol / L Ni₂SO₄·6H₂O, 0.1 mol / L AgNO₃·6H₂O, 0.06 mol / L Co(SO₄)₂·7H₂O, 0.06 mol / L LdCl₂·H₂O, 0.08 mol / L InCl₃·4H₂O, and 0... 0.1 mol / L LYCl3, 0.04 mol / L HfCl4, 0.04 mol / L TaCl5, and 0.012 mol / L ascorbic acid were dissolved sequentially in solution A above. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH of the solution was then adjusted to 3 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 2 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 100 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiAgCoCdInYHfTa high-entropy alloy layer and a NiAgCoCdInYHfTa-C high-entropy alloy electrode sheet.

[0055] Example 8

[0056] A method for preparing a high-entropy alloy material, comprising the following steps:

[0057] A 2×2cm carbon cloth substrate was etched in concentrated acid (H₂SO₄ and HNO₃) for 3 hours, with a volume ratio of H₂SO₄ to HNO₃ of 2:1, to obtain a hydrophilic carbon cloth product. The hydrophilic carbon cloth was then ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At 50℃, 0.008 mol / L sodium dodecyl sulfate, 0.015 mol / L boric acid, and 0.09 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. 0.06 mol / L Ni₂SO₄·6H₂O, 0.1 mol / L AgNO₃·6H₂O, 0.06 mol / L Co(SO₄)₂·7H₂O, 0.06 mol / L LdCl₂·H₂O, 0.08 mol / L InCl₃·4H₂O, and 0... 0.1 mol / L LYCl3, 0.04 mol / L HfCl4, 0.04 mol / L TaCl5, and 0.012 mol / L ascorbic acid were dissolved sequentially in solution A above. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH of the solution was then adjusted to 6.8 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 2 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiAgCoCdInYHfTa high-entropy alloy layer and a NiAgCoCdInYHfTa-C high-entropy alloy electrode sheet.

[0058] Example 9

[0059] A method for preparing a high-entropy alloy material, comprising the following steps:

[0060] A 2×2cm carbon cloth substrate was etched in concentrated acid (H₂SO₄ and HNO₃) for 3 hours, with a volume ratio of H₂SO₄ to HNO₃ of 2:1, to obtain a hydrophilic carbon cloth product. The hydrophilic carbon cloth was then ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At 30℃, 0.003 mol / L sodium dodecyl sulfate, 0.005 mol / L boric acid, and 0.09 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. The concentrations of the metal salts were adjusted to 0.006 mol / L Ni₂SO₄·6H₂O, 0.008 mol / L AgNO₃·6H₂O, 0.006 mol / L Co(SO₄)₂·7H₂O, 0.008 mol / L CdCl₂·H₂O, and 0.005 mol / L InCl₃· 4H₂O, 0.009 mol / L LYCl₃, 0.006 mol / L HfCl₄, 0.006 mol / L TaCl₅, and 0.012 mol / L ascorbic acid were dissolved sequentially in solution A above. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH of the solution was then adjusted to 3 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 2 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiAgCoCdInYHfTa high-entropy alloy layer and a NiAgCoCdInYHfTa-C high-entropy alloy electrode sheet.

[0061] Comparative Example 1

[0062] A method for preparing a high-entropy alloy material, comprising the following steps:

[0063] A 2×2cm nonwoven fabric backing was used directly without pretreatment. At room temperature, 0.078 mol / L sodium dodecyl sulfate, 0.12 mol / L boric acid, and 0.1 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. 0.05 mol / L Ni₂SO₄·6H₂O, 0.08 mol / L AgNO₃·6H₂O, 0.05 mol / L Co(SO₄)₂·7H₂O, 0.08 mol / L LdCl₂·H₂O, and 0.05 mol / L Li₂SO₄·6H₂O were then added. In solution A, nCl3·4H2O, 0.06 mol / L LYCl3, 0.05 mol / L HfCl4, 0.03 mol / L TaCl5, and 0.12 mol / L ascorbic acid were dissolved sequentially. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH was then adjusted to 3 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 2 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiAgCoCdInYHfTa high-entropy alloy layer and a NiAgCoCdInYHfTa-C high-entropy alloy electrode sheet.

[0064] Comparative Example 2

[0065] A method for preparing a high-entropy alloy material, comprising the following steps:

[0066] A 2×2cm carbon cloth substrate was etched in concentrated acid H2SO4 and HNO3 for 3 hours, with a volume ratio of H2SO4 to HNO3 of 2:1, to obtain a surface hydrophilic carbon cloth product. The hydrophilic carbon cloth was then repeatedly ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At room temperature, 0.081 mol / L Ni₂SO₄·6H₂O, 0.14 mol / L AgNO₃·6H₂O, 0.061 mol / L Cd(NO₃)₂·4H₂O, 0.06 mol / L Cu(NO₃)₂·9H₂O, and 0.09 mol / L In(NO₃)₃·5H₂O were sequentially dissolved in deionized water. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH of the solution was then adjusted to 2.8 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 1 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 15 min, resulting in a NiAgCdCuIn alloy layer and a NiAgCdCuIn-C alloy electrode sheet based on electrodeposition.

[0067] Comparative Example 3

[0068] A 2×2cm carbon cloth substrate was etched in concentrated acid H2SO4 and HNO3 for 3 hours, with a volume ratio of H2SO4 to HNO3 of 2:1, to obtain a surface hydrophilic carbon cloth product. The hydrophilic carbon cloth was then repeatedly ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At room temperature, 0.009 mol / L sodium dodecylbenzenesulfonate, 0.014 mol / L boric acid, and 0.092 mol / L citric acid were dissolved in 100 mL of deionized water to obtain mixed solution A. 0.09 mol / L Ni₂SO₄·6H₂O, 0.12 mol / L In(NO₃)₃·5H₂O, and 0.09 mol / L Cd(NO₃)₂·4H₂O were dissolved in solution A in sequence. The solution was stirred at 50 °C for 0.5 h. After all reagents were dissolved, the pH of the solution was adjusted to 2.8 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 1 h, an electrochemical deposition reaction was carried out at 25 °C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 15 min, resulting in a NiInCd alloy layer and a NiInCd-C alloy electrode based on electrodeposition.

[0069] Comparative Example 4

[0070] A method for preparing a high-entropy alloy material, comprising the following steps:

[0071] A 2×2cm carbon cloth substrate was etched in concentrated acid (H₂SO₄ and HNO₃) for 3 hours, with a volume ratio of H₂SO₄ to HNO₃ of 2:1, to obtain a hydrophilic carbon cloth product. The hydrophilic carbon cloth was then ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At room temperature, 0.01 mol / L sodium dodecyl sulfate, 0.02 mol / L boric acid, and 0.032 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. The types and concentrations of metal salts were adjusted to 0.05 mol / L Ni₂SO₄·6H₂O, 0.06 mol / L Na₂SO₄, and 0.04 mol / L... MnSO4·H2O, 0.08 mol / L FeSO4·7H2O, 0.1 mol / L AlCl3·6H2O, 0.04 mol / L CaSO4·2H2O, 0.02 mol / L TiCl4, and 0.012 mol / L ascorbic acid were dissolved sequentially in solution A. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH was then adjusted to 3 to obtain electrodeposition solution B. A constant current electrodeposition method was used. After the electrodeposition solution was allowed to stand for 2 h, an electrochemical deposition reaction was carried out at 25°C using a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode, with a current density of 3 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiNaMnFeAlCaTi high-entropy alloy layer and a NiNaMnFeAlCaTi-C high-entropy alloy electrode sheet based on electrodeposition.

[0072] Comparative Example 5

[0073] A method for preparing a high-entropy alloy material, comprising the following steps:

[0074] A 2×2cm carbon cloth substrate was etched in concentrated acid H2SO4 and HNO3 for 3 hours, with a volume ratio of H2SO4 to HNO3 of 2:1, to obtain a surface hydrophilic carbon cloth product. The hydrophilic carbon cloth was then repeatedly ultrasonically cleaned three times in acetone and deionized water to obtain a pH-neutral hydrophilic carbon cloth for later use. At 50℃, 0.16 mol / L sodium dodecyl sulfate, 0.015 mol / L boric acid, and 0.29 mol / L citric acid were successively dissolved in 100 mL of deionized water to obtain mixed solution A. The types and concentrations of metal salts were adjusted to 0.3 mol / L Ni₂SO₄·6H₂O, 0.2 mol / L Na₂SO₄, 0.1 mol / L MnSO₄·H₂O, 0.15 mol / L ZnSO₄·7H₂O, 0.45 mol / L InCl₃·4H₂O, 0.6 mol / L LYCl₃, 0.4 mol / L TiCl₄, and 0.3 mol / L LYCl₃. TaCl5 and 0.012 mol / L ascorbic acid were dissolved sequentially in solution A above. The solution was stirred at 50°C for 0.5 h until all reagents were dissolved. The pH of the solution was then adjusted to 3 to obtain electrodeposition solution B. Using a constant current electrodeposition method, after the electrodeposition solution was allowed to stand for 2 h, an electrochemical deposition reaction was carried out at 25°C with a graphite electrode as the counter electrode and hydrophilic carbon cloth as the working electrode. The current density was 3 mA / cm². 2 The electrodeposition time was 10 min, resulting in a NiNaMnZnInYTiTa high-entropy alloy layer and a NiNaMnZnInYTiTa-C high-entropy alloy electrode sheet based on electrodeposition.

[0075] Test case

[0076] The alloy electrodes prepared in Examples 1-9 and Comparative Examples 1-5 were subjected to lithium cycle tests and rate tests. The specific testing process is as follows: the prepared alloy electrodes were cut to suitable sizes, vacuum dried, and then lithium metal and the alloy electrodes were assembled into solid-state coin cells. The cells were then tested at room temperature (25°C) with a current density of 30 mA / cm². 2 The verification test results are shown in Table 1:

[0077] Table 1

[0078]

[0079] As shown in Table 1, the test data results reveal that when the metal salt concentration is low, the amount of metal alloy deposited per unit area of ​​substrate is limited. This not only hinders the formation of high-entropy alloys but also negatively impacts the uniformity and density of alloy deposition. Furthermore, under these conditions, the alloy anode cannot effectively lower the lithium-ion migration barrier, resulting in a reduced number of available lithium deposition sites and thus hindering the lithium-ion transport rate. Comparing Example 3 with Comparative Example 5, when the metal salt and additive concentrations are too high, excessive metal electrodeposition occurs, leading to uneven deposition of the alloy anode. An excessively thick alloy layer restricts the lithium-ion transport rate, significantly increasing the electrode interface impedance, inducing lithium dendrite growth, and ultimately causing a short circuit in the battery. Additionally, the comparison between Example 3 and Comparative Example 4 indicates that the doping of rare earth metals and rare dispersed metals has a significant impact on the electrochemical performance of high-entropy alloys.

[0080] In summary, the key factors in the electrodeposition preparation of high-entropy alloy electrodes are the different valence states and types of soluble metal salts. High-entropy alloys containing rare earth metals and rare dispersed metals possess high corrosion resistance and high plasticity. The regulation of multi-metals with different valence states results in a more disordered entropy structure and more uniform deposition of the prepared alloy, which can effectively improve the stability and electrochemical characteristics of battery cycle testing. Meanwhile, the concentration of metal salts and the content of additives (surfactants, buffers, reducing agents) are also key factors affecting the uniform electrodeposition preparation of high-entropy alloys. Within a reasonable range of metal content ratios, the prepared high-entropy alloys exhibit high capacity retention and good cycle stability in lithium batteries, maintaining a high coulombic efficiency. Combined with Comparative Examples 1-3, it was found that the hydrophilicity and conductivity of the substrate material also directly affect the alloy layer deposition effect. Furthermore, it was demonstrated that high-entropy structural alloy materials prepared from five or more metals possess high strength, high corrosion resistance, and high thermal stability. When applied to lithium metal batteries, they significantly improve problems such as dendrite growth and battery cycle stability in lithium metal batteries.

[0081] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A high-entropy alloy electrode, characterized in that, Includes a substrate and a high-entropy alloy deposited on the substrate, the high-entropy alloy having the general chemical formula Ni. 20 M a N b X c Y d Z e It includes rare earth metals and / or rare dispersed metals, where a, b, c, d, and e represent the atomic percentages of the corresponding metal elements, wherein 5≤a≤35; 10≤b≤40; 6≤c≤35; 0.1≤d≤10; 0≤e≤10; a+b+c+d+e=80; M is a monovalent metal, N is a divalent metal, X is a trivalent La-series metal, Y is a tetravalent metal, and Z is a pentavalent metal.

2. The high-entropy alloy electrode sheet according to claim 1, characterized in that, M is selected from one or more of Li, Na, and Ag; N is selected from one or more of Fe, Co, Cu, Zn, Mn, Mo, Ho, Cd, Mg, Ca, Sn, and Ba; X is selected from one or more of Al, Ga, In, Yb, Y, and Sc; Y is selected from one or more of Zr, Hf, and Ti; and Z is selected from one or more of Ta, V, and Nb.

3. The method for preparing the high-entropy alloy electrode sheet according to claim 1 or 2, characterized in that, Includes the following steps: (1) Dissolve the surfactant, buffer and complexing agent in deionized water to obtain mixed preparation solution A; (2) Dissolve five or more soluble metal salts and reducing agents in solution A, and adjust the pH to obtain electrodeposition solution B; (3) The substrate material is placed in electrodeposition solution B for constant current electrodeposition to obtain high entropy alloy electrode sheets.

4. The method for preparing high-entropy alloy electrodes according to claim 3, characterized in that, The surfactant is one or more of stearic acid, sodium dodecylbenzenesulfonate, sulfated castor oil, sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, polyethyleneimine, polyvinyl alcohol, alkylphenol polyoxyethylene ether, and triethanolamine; the buffer is one or more of boric acid, acetic acid, acetic acid, sodium acetate, disodium hydrogen phosphate, sodium dihydrogen phosphate, 2-morpholine ethanesulfonic acid, and sodium carbonate; the complexing agent is one or more of citric acid, citric acid hydrate, trisodium citrate, sodium cyanide, potassium pyrophosphate, sodium pyrophosphate, ethylenediamine, triethanolamine, oxalic acid, and gluconic acid; and the reducing agent is one or more of ascorbic acid, sodium phosphite, sodium saccharin, dimethylamineborane, sodium borohydride, sodium hypophosphite, and formaldehyde.

5. The method for preparing high-entropy alloy electrodes according to claim 4, characterized in that, The soluble metal salt is a Ni-containing metal ion. + M + N 2+ X 3+ Y 4+ Z 5+ One or more of the following: chloride salts, chloride salt hydrates, nitrates, nitrate salt hydrates, sulfates, and sulfate salt hydrates.

6. The method for preparing high-entropy alloy electrodes according to claim 5, characterized in that, The concentrations of soluble metal salts in the electrodeposition solution B are as follows: nickel salt 0.005–0.61 mol / L, M salt 0.001–0.82 mol / L, N salt 0.004–0.86 mol / L, X salt 0.0035–0.5 mol / L, Y salt 0.0005–0.1 mol / L, Z salt 0.0003–0.1 mol / L; surfactant concentration 0.002–0.15 mol / L; buffer concentration 0.006–0.43 mol / L; complexing agent concentration 0.004–0.28 mol / L; and reducing agent concentration 0.001–0.18 mol / L.

7. The method for preparing high-entropy alloy electrodes according to claim 6, characterized in that, The substrate material is one or more of the following: copper foil, copper sheet, titanium sheet, silver rod, platinum sheet, copper foam, nickel foam, carbon cloth, non-woven fabric, carbon paper, carbon fiber, and porous carbon paper.

8. The method for preparing high-entropy alloy electrodes according to claim 7, characterized in that, In step (3), the substrate material is etched in advance using an acidic solution, which is one or more of concentrated sulfuric acid, concentrated nitric acid, and concentrated hydrochloric acid.

9. The method for preparing high-entropy alloy electrodes according to claim 8, characterized in that, The constant current electrodeposition temperature is 20-120℃, and the current density is 1-3800 mA / cm². 2 The time is 0.05-12h, the graphite electrode is the counter electrode, and the substrate material is the working electrode.

10. The application of the high-entropy alloy electrode as described in claim 1 or 2 in lithium metal batteries.

Citation Information

Patent Citations

  • High-entropy alloy structured composite negative electrode material, preparation method thereof and lithium metal battery

    CN119419256A

  • Preparation method of lithium metal negative electrode with ultrathin lithium-loving high-entropy alloy interface layer

    CN119447197A